Enhancement of magnetocaloric effect by external hydrostatic pressure in MnNi0.75Fe0.25Ge alloy. (9th May 2018) - Mandal, K; Dutta, P; Dasgupta, P; Pramanick, S; Chatterjee, S
Abstract: A systematic investigation on the structural and magnetic properties of an Fe-doped MnNiGe alloy with nominal composition MnNi0.75 Fe0.25 Ge has been performed. Temperature dependent x-ray diffraction studies indicate a clear structural phase transition (martensitic type) from the high temperature hexagonal austenite phase (space group P 63 / mmc ) to the low temperature orthorhombic martensite phase (space group Pnma ). Interestingly, about 1.4% of the high temperature hexagonal phase has been observed at 15 K, which is well below the martensitic phase transition (MPT) temperature. The studied alloy is found to be ferromagnetic in nature at the lowest temperature of measurement and the saturation moment increases in the presence of external hydrostatic pressure ( P ). In addition, it shows a significantly large conventional (negative) magnetocaloric effect with an adiabatic entropy change ( ) of about −16.2 J kg −1 K −1 around the MPT for a magnetic field changing from 0  →  5 T. The most interesting observation is the  ̃40.1% increase in the peak value of on application of 6 kbar of external P . A considerable increment in the refrigeration capacity has also been noted with the applied P .